THE IMPORTANCE OF COMMUNICATIVE COMPETENCE IN TEACHING ENGLISH FOR SPECIFIC PURPOSES (ESP) - G’ulomjonova Mohibonu G’ayratjonovna, (Ta'lim innovatsiyasi va integratsiyasi, 2026)
Abstract This article explores the importance of communicative competence in Teaching English  for  Specific  Purposes  (ESP),  particularly  for  non-philological  students.  In modern  higher  education,  learners  from  technical  and  non-linguistic  fields  require English not only for academic purposes but also for professional communication. The study  discusses  key  theoretical  frameworks  of  communicative  competence  and examines  its  role  in  ESP  classrooms.  The  research  highlights  that  communicative competence improves students’ ability to use English in real-life professional contexts, enhances speaking confidence, and supports task-based learning. The findings suggest that integrating communicative activities into ESP instruction significantly increases learners’ linguistic and pragmatic performance.